Prevalence and risk factors for post-investigation colorectal cancer (“interval cancer”) after computed tomographic colonography: protocol for a systematic review - Andrew Plumb; Anu Obaro; Thomas Fanshawe; Ulysses S. Torres; Rachel Baldwin‐Cleland; Steve Halligan; David Burling (2017)
Colorectal cancer (CRC) is a common and important disease. There are different tests for diagnosis, one of which is computed tomographic colonography (CTC). No test is perfect, and patients with normal CTC may subsequently develop CRC (either because it was overlooked originally, or because it has developed in the interim). This is termed post-investigation colorectal cancer (PICRC) or "interval cancer". How frequently this occurs after CTC is not known. The purpose of this systematic review and meta-analysis is to use the primary literature to estimate the PICRC rate after CTC, and explore associated factors.Primary studies reporting post-investigation colorectal cancer (PICRC) rates after CTC will be identified from PubMed, Embase and Cochrane Register of Controlled Trials databases. Peer-reviewed studies published after 1994 (the year CTC was introduced) will be included and the rate of PICRC within 36 months of CTC recorded. Data will be extracted from selected studies for a random effects meta-analysis. Heterogeneity, risk of bias and publication bias will be assessed, and exploratory analysis will examine factors associated with higher PICRC rates in the literature.PICRC rates are the ultimate benchmark of diagnostic quality for colonic investigations. This systematic review and meta-analysis will identify and synthesise evidence to determine PICRC rates after CTC and explore factors that may contribute to higher rates.PROSPERO (registration number CRD42016042437 ).